TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN KEWAJIBAN BLU DI INDONESIA: (Studi Literatur 2022–2025) - Amelia Putri Nurchoiriyah; Emeliatus Sofia; Fathul Beri; Mohamad Djasuli (Politeknik Negeri Ambon, 2025)
Introduction: This study is a literature review that aims to analyze the importance of transparency and accountability in the management of obligations by Public Service Agencies (BLU) in Indonesia. As government entities granted financial flexibility, BLUs require strong oversight to remain accountable in carrying out their public service mandates. Methods: This study employs a qualitative approach using a literature review method, drawing upon academic publications, government regulations, and audit reports. The aim is to synthesize various findings related to the financial governance of BLU and assess the effectiveness of current oversight mechanisms. Results: The findings reveal that a major governance challenge lies in the mismatch between budget flexibility and suboptimal reporting systems. Additionally, the limited human resource capacity in financial management has a negative impact on transparency and accountability. The study highlights the need for integrated financial information systems, capacity-building training, and strengthened internal oversight mechanisms to ensure that BLU obligations are managed in accordance with good governance principles. Keywords: Public Service Agency, Transparency, Accountability, Obligations, Public Financial Management